Uma an??lise da din??mica do setor el??trico brasileiro utilizando VAR em painel - Brand??o, Lucas Guimar??es Lins (2017)
This study estimates the interrelation between selected variables of the Brazilian electric sector and the Brazilian economy. Using monthly data from the submarkets (Southeast / Center-West, South, Northeast and North) and the Brazilian economy, these qualify these relationships through the panel vector autoregression (PVAR) methodology and impulse response. This method has the quality to evaluate the response of the several variables to the disturbances, without giving focus to a mathematical modeling. It is identified that the Brazilian energy market has a rigidity of the distributors' energy tariff, which can be explained by the state's regulatory intervention. Futhermore there is a relationship between consumption and energy tariff, however, this is not directly related to the short-term market price.